Technique to assess the alveolar bone width for immediate implant placement in fresh extraction sockets - Neeraj Kumar Chandraker; Ramesh Chowdhary; Abha Verma (Wolters Kluwer Medknow Publications, 2013)
Aim: To determine labial and lingual plate width at extraction site, using extracted tooth. Materials and Methods: Pre-extraction ridge mapping and arch impression using putty consistency elastomeric impression material is recorded, followed by atraumatic tooth extraction, extracted tooth is cleaned and reoriented in the earlier recorded elastomeric putty impression. The cast obtained is used to measure bone width. Results: The amount of available labial and palatal bone of an extracted socket can be assessed accurately. Conclusion: This technique will help the surgeon understand the thickness of labial plate especially the apical region without reflecting the flap, also aid in selection of proper dimension of dental implant, and if bone graft is needed.